Green Productivity in Increasing the Productivity of Sugar Cane Farmers and Reducing Impacts on the Environment - Inggit Marodiyah; Hana Catur Wahyuni; Intan Rohma Nurmalasari (Universitas Muhammadiyah Sidoarjo, 2023)
This research aims to improve the productivity and environmental performance of sugarcane farming through sustainable enhancements. Utilizing the Cobb-Douglas method, factors influencing sugarcane farming management and green productivity are identified to reduce environmental impacts. The study highlights the significance of environmental aspects in the agricultural sector and proposes green productivity as a strategy to increase awareness and address land-related environmental concerns. The results show that by implementing green productivity practices, sugarcane productivity can be augmented, management costs reduced, and farmers' income increased, leading to a more sustainable and high-quality agricultural sector. Highlights: Increased Productivity: Implementing green productivity strategies in sugarcane farming to enhance crop yields and profitability. Sustainable Agriculture: Addressing environmental concerns through eco-friendly practices in sugarcane cultivation for long-term viability. Cobb-Douglas Method: Utilizing a robust analytical approach to identify influential factors and optimize sugarcane farming management. Keywords: Green Productivity, Sugarcane Farming, Cobb-Douglas Analysis, Sustainability, Environmental Impact.